2021
DOI: 10.1108/bjm-10-2020-0367
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities: interrelations and distinct effects on performance in low and high competitive intensity environments

Abstract: PurposeThis study aims to augment the understanding of dynamic capabilities (DCs) by exploring the interrelations among the DC categories (sensing, seizing, reconfiguring) and the distinct impact of each DC on firm performance under low and high levels of competitive intensity.Design/methodology/approachThe analysis is based on a cross-sectional survey of 139 managers in Israel. The data were collected through Web-based questionnaires using the Qualtrics software. A two-stage data analysis was performed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
1
7
0
Order By: Relevance
“…Our results show that OCs are indeed strongly related to GP and that EO and DMCs strongly antecede OCs, in line with their theoretical formulation [3,25,26]. However, CI is not a significant moderator in any relationship with GP, at any level of CI, determined through a marginal effects analysis [27][28][29]. Finally, the DMC's and EO's relationships with GP are entirely mediated by OCs.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results show that OCs are indeed strongly related to GP and that EO and DMCs strongly antecede OCs, in line with their theoretical formulation [3,25,26]. However, CI is not a significant moderator in any relationship with GP, at any level of CI, determined through a marginal effects analysis [27][28][29]. Finally, the DMC's and EO's relationships with GP are entirely mediated by OCs.…”
Section: Introductionsupporting
confidence: 81%
“…While we concluded that age was not a significant control and CI a nonsignificant or non-substantive moderator, further studies should consider other environmental variables. Market and technological turbulence have long since been a staple moderator within models considering DCs [28,40,115], although little research exists about them with consideration to microenterprises. Despite having reason to believe these findings are generalizable to similar institutional environments, further empirical confirmation is needed on this front.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Second, unlike previous studies that explored individual dynamic capabilities (Bingham, Heimeriks, Schijven, & Gates, 2015), our research provides insights into the links among dynamic capabilities. Previous studies found no direct impact of sensing on performance (Markovich, Efrat, & Raban, 2021), but we conclude that the true value of sensing is its mediation of the effect of information sources on seizing and reconfiguring, both of which have been shown to enhance firms' performance (Wilden et al, 2013). In this respect, we advance on Bingham et al, (2015) in explaining the development of all three types of dynamic capabilities in parallel, based on sensing.…”
Section: Theoretical Implicationsmentioning
confidence: 77%
“…Dynamic capabilities are second-order organizational capabilities aimed at achieving competitive advantage through generating and modifying firms' routines and practices (Zollo & Winter, 2002). Dynamic capabilities are especially relevant for achieving sustainable competitive advantage and maximizing long-term performance in changing and turbulent environments (Arndt & Bach, 2015;Corner & Kearins, 2018;Efrat, Hughes, Nemkova, Souchon, & Sy-Changco, 2018;Markovich, Efrat, & Raban, 2021;Teece, 2007Teece, , 2012Teece, , 2018aTeece, , 2018bTorres, Sidorova, & Jones, 2018;Wang & Ahmed, 2007;Williamson, 2016). They 'enable the firm to integrate, build, and reconfigure internal and external resources to maintain leadership in continually shifting business environments' (Teece, 2014, p. 329).…”
Section: Introductionmentioning
confidence: 99%
“…Although challenging, the firms good in alliance management can realize the potential benefits of a given alliance (Markovich et al , 2021; Schilke, 2014). Therefore, a research stream emerges focusing on how a focal firm can develop and augment its “capabilities” of managing alliances [1] effectively, and what effect these capabilities have on alliance performance (Kauppila, 2015).…”
Section: Introductionmentioning
confidence: 99%